2020
DOI: 10.3311/ppci.16166
|View full text |Cite
|
Sign up to set email alerts
|

Effective Stress and Compressibility of Unsaturated Clayey Soil under Drying and Wetting Cycles

Abstract: Naturally, soil moisture reduces during dry seasons when the soil is in drying state; while it increases during wet seasons when the soil is in wetting state. Previous studies have shown that for an unsaturated soil sample, soil-water characteristic curves (SWCCs) do not match in wetting and drying paths. The differences between wetting and drying paths are called the hydraulic hysteresis. The hydraulic hysteresis plays an important role in mechanical properties of soil such as shear strength, volume change, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The determined soil water characteristic curves are shown in Figure 4. Some scholars have measured the moisture characteristic curve of clay in two different processes of wetting and drying found that under the same water content, the matric suction in the drying process is always greater than that in the wetting process (Kholghifard, 2020;Ding et al, 2022;Sarker and Wang, 2022). Figure 4 shows that the drying curves are above the wetting curves for specimens with both 5% lime and 8% lime contents.…”
Section: Effect Of Water Content Change Pathmentioning
confidence: 94%
See 1 more Smart Citation
“…The determined soil water characteristic curves are shown in Figure 4. Some scholars have measured the moisture characteristic curve of clay in two different processes of wetting and drying found that under the same water content, the matric suction in the drying process is always greater than that in the wetting process (Kholghifard, 2020;Ding et al, 2022;Sarker and Wang, 2022). Figure 4 shows that the drying curves are above the wetting curves for specimens with both 5% lime and 8% lime contents.…”
Section: Effect Of Water Content Change Pathmentioning
confidence: 94%
“…In terms of macroscopic mechanical properties, matric suction is closely correlated with the shear strength of the soil. The relationship between matric suction and water content is described using the soil-water characteristic curve (SWCC), and scholars such as Bishop has established connections between matric suction and the strength of unsaturated soils (Kholghifard, 2020;Zhao et al, 2021). Several factors have been demonstrated to affect the SWCC, Gallage and Uchimura (2010) indicated that soils with low density exhibit lower residual suction compared to those with high density, while the influence of soil structure on SWCC can be negligible in the high suction range (Baker and Frydman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have proposed that chemical composition analysis theory and the damage mechanics method can effectively analyze chemical damage mechanisms in water-rock interaction [18][19][20]. The water-rock interaction has a significant time effect on the mechanical parameters of rocks, and its effect varies for different rocks [21][22][23]. It was found that an aqueous environment with higher OH − concentration causes a significant increase in the growth rate of quartz fracture [24,25].…”
Section: Introductionmentioning
confidence: 99%